Predictors of Repeated Visits to a Pediatric Emergency Department Crisis Intervention Program. Issue 2 (30th August 2016) - Cloutier, P.; Thibedeau, N.; Barrowman, N.; Gray, C.; Kennedy, A.; Leon, S.L.; Polihronis, C.; Cappelli, M.
Abstract: Objectives: Despite documented increases in emergency department (ED) mental health (MH) presentations, there are inconsistent findings on the characteristics of patients with repeat presentations to pediatric EDs (PEDs) for MH concerns. Our study sought to explore the characteristics of MH patients with repeat PED visits and determine predictors of return visits, of earlier repeat visits, and of more frequent repeat visits. Methods: We examined data collected prospectively in a clinical database looking at MH presentations to a crisis intervention program housed within a PED from October 2006 to December 2011. Predictive models based on demographic and clinical variables were constructed using logistic, Cox, and negative binomial regression. Results: A total of 4, 080 presentations to the PED were made by the 2, 900 children and youth. Repeat visits accounted for almost half (45.8%) of all presentations. Multivariable analysis identified five variables that independently predicted greater odds of having repeat presentations, greater risk of earlier repeat presentations, and greater risk of frequent repeat presentations. The five variables were: female, living in the metropolitan community close to the PED, being in the care of child protective services, taking psychotropic medications, and presenting with an actionable need in the area of mood disturbances. Conclusions: Repeat visits account for a large portion of all MH presentations to the PED. Furthermore, several patient characteristics are significant predictors of repeat PED use and of repeating use sooner and more frequently. Further research is needed to examine interventions targeting this patient group to ensure appropriate MH patient management. RÉSUMÉ: Objectifs: Malgré une augmentation confirmée des cas de troubles mentaux (TM) au service des urgences, il existe des divergences quant aux caractéristiques des patients qui consultent de nouveau au service des urgences pédiatriques (SUP) pour des TM. L'étude décrite ici visait à examiner les caractéristiques des patients qui retournaient au SU pédiatrique pour des TM, et à déterminer les variables prévisionnelles de reconsultation, de reconsultation précoce ou de reconsultation fréquente. Méthodes: Les auteurs ont procédé à un examen de données prospectives, recueillies d'octobre 2006 à décembre 2011 dans une base de données cliniques portant sur des TM, dans le cadre d'un programme d'intervention en cas de crise, établi dans un SUP. Des modèles prévisionnels, fondés sur des variables démographiques et cliniques ont été élaborés à l'aide de régressions logistiques, de régression de Cox et de régressions binomiales négatives. Résultats: Au total, 4080 consultations au SUP ont été réalisées pour 2900 enfants et jeunes. Les reconsultations représentaient presque la moitié (45, 8 %) de toutes les consultations. L'analyse multidimensionnelle a permis de cerner cinq variables indépendantes, prévisionnelles d'un risque accru de reconsultation, de reconsultation précoce ou de reconsultation fréquente; il s'agit du fait d'être une femme, de vivre dans la grande agglomération près du SUP, de relever des services de protection de l'enfance, de prendre des psychotropes et d'avoir des besoins nécessitant des interventions relatives aux troubles de l'humeur. Conclusions: Les reconsultations représentent une grande part de toutes les consultations faites au SUP pour des TM. En outre, plusieurs caractéristiques des patients sont des variables prévisionnelles importantes de reconsultation au SUP, de reconsultation précoce ou de reconsultation fréquente. Il faudrait mener d'autres études sur des interventions ciblant ce groupe particulier de patients afin que les TM fassent l'objet d'une prise en charge appropriée.